Creativity as a Methodological dimension of Social Research between Quantity and Quality - Sacchetti, Francesco (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2019)
In this work I address creativity in the process of social sciences research, comparing quantitative and qualitative approaches. In discussing creativity I go back to Chomsky and his distinction between rule-governed and rule-changing creativity. In my analysis I suggest that the quantitative approach is characterized by rule-governed creativity, the qualitative one by rule-changing creativity: these are two models of creativity that the Chomskian vision links to a set of rules. Thus in the first case the creation of the tools by which the researcher collects information is submitted to a set of rules related to substantial and procedural competences. In the second case the creative phase does not have a place in the creation of a tool, but rather in a performance. The idea of performance as a constitutive part in qualitative research is analysed on a substantial basis, revealing the implications of distinct creative processes under different methodological choices. Whilst a quantitative approach requires using procedural and substantial competences, I suggest that in a qualitative enquiry the researcher’s fieldwork is considered as a ‘performance’ because of its adaptive character. The researcher is constantly confronted with unforeseen situations, surrounded by an unknown environment. Also, this use of the notion of ‘performance’ comprehends both elements of the process as well as of the outcome of fieldwork, as it recalls peculiar characteristics of qualitative work: action and interaction, personal involvement and, above all, orientation to a purpose (in this context, the teleological purpose of knowledge production).